2010
DOI: 10.1007/s11892-010-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Characterization of Type 2 Diabetes–Related Loci

Abstract: For the past two decades, genetics has been widely explored as a tool for unraveling the pathogenesis of diabetes. Many risk alleles for type 2 diabetes and hyperglycemia have been detected in recent years through massive genome-wide association studies and evidence exists that most of these variants influence pancreatic β-cell function. However, risk alleles in five loci seem to have a primary impact on insulin sensitivity. Investigations of more detailed physiologic phenotypes, such as the insulin response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 82 publications
(84 reference statements)
3
40
0
Order By: Relevance
“…The hypothesis of a potential association between common variation in OxPhos genes and type 2 diabetes was strongly supported a priori by numerous metabolic and physiological studies [7][8][9][10][11][12][13][14][15][16][17][18]. This makes our study unique compared with replication studies and meta-analysis of previously identified type 2 diabetes risk alleles, for most of which knowledge of the underlying phenotype leading to type 2 diabetes is limited [23]. The present study is, to our knowledge, the first to replicate a nominal association between OxPhos gene variants and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The hypothesis of a potential association between common variation in OxPhos genes and type 2 diabetes was strongly supported a priori by numerous metabolic and physiological studies [7][8][9][10][11][12][13][14][15][16][17][18]. This makes our study unique compared with replication studies and meta-analysis of previously identified type 2 diabetes risk alleles, for most of which knowledge of the underlying phenotype leading to type 2 diabetes is limited [23]. The present study is, to our knowledge, the first to replicate a nominal association between OxPhos gene variants and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 52%
“…However, it remains to be established whether mitochondrial dysfunction is a cause or consequence of insulin resistance and/or beta cell dysfunction in type 2 diabetes. To date, genome-wide association (GWA) studies have shown 38 common genetic variants to be robustly associated with type 2 diabetes, with 16 additional loci associated with traits of glucose homeostasis [23]. Together, they explain approximately 10% of type 2 diabetes heritability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, our data extend previous molecular-genetic studies that tested association of T2DM SNPs with CAD. (10;38)…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the selected variants were scanned for the previously introduced gene set implicated in glucose metabolism [12]. These are the genes with an essential role in pancreatic beta cells, genes previously known to cause monogenic diabetes or associated syndromes and genes from the genome-wide association data of type 2 diabetes [19,20,21,22,23,24,25,26]. The list of genes of interest is shown in table 2.…”
Section: Methodsmentioning
confidence: 99%